2018
DOI: 10.1063/1.5020918
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage, large-strain soft electrothermal actuators based on laser-reduced graphene oxide/Ag particle composites

Abstract: In this paper, low-voltage, large-strain flexible electrothermal actuators (ETAs) based on laser-reduced graphene oxide (LRGO)/Ag particle composites were fabricated in a simple and cost-efficient process. By adding Ag particles to the LRGO, the sheet resistance decreased effectively. Under a driving voltage of 28 V, the actuator obtained a bending angle of 192° within 6 s. Besides, the bending deformation could be precisely controlled by the driving voltage ranging from 10° to 192°. Finally, a gripper compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…f Comparison of actuating speed as function of voltage. 1: Cellulose/ionic liquid/graphene 46 ; 2: Poly(styrene-alt-maleimide)/poly(vinylidene fluoride) 40 ; 3: Poly(3,4-ethylenedioxythiophene)/ poly(styrene sulfonate)/ ionic liquids 47 ; 4: Chitosan/CNT 39 ; 5: rGO/epoxy 42 ; 6: Polyurethane/CNT 45 ; 7: CNT/carbon black 41 ; 8: Polycyclooctene/CNT 42 ; 9: Polyethylene/CNT 43 ; 10: rGO/polyimide 49 ; 11: MoS 2 /Au; 51 12: PP/cellulose 48 ; 13: Graphene/Ag/polyimide 50 …”
Section: Resultsmentioning
confidence: 99%
“…f Comparison of actuating speed as function of voltage. 1: Cellulose/ionic liquid/graphene 46 ; 2: Poly(styrene-alt-maleimide)/poly(vinylidene fluoride) 40 ; 3: Poly(3,4-ethylenedioxythiophene)/ poly(styrene sulfonate)/ ionic liquids 47 ; 4: Chitosan/CNT 39 ; 5: rGO/epoxy 42 ; 6: Polyurethane/CNT 45 ; 7: CNT/carbon black 41 ; 8: Polycyclooctene/CNT 42 ; 9: Polyethylene/CNT 43 ; 10: rGO/polyimide 49 ; 11: MoS 2 /Au; 51 12: PP/cellulose 48 ; 13: Graphene/Ag/polyimide 50 …”
Section: Resultsmentioning
confidence: 99%
“… 50 Meanwhile, laser technologies are capable of high-efficiency, mask-free patterning, and hierarchical structuring of graphene, which is of benefit to the design and fabrication of electrothermal actuators. As typical examples, RGO- or LIG-based electrothermal actuators, including LRGO/PI, 122 Ag-LRGO/PI, 123 LRGO/polyethylene (LRGO/PE), 124 PI/LIG/PVDF, 125 GO/RGO/tape, 126 and PI/LIG/PDMS 39 structures have been successfully developed, demonstrating sophisticated deformation ability. The hierarchical structure of graphene plays an important role for the performances of ERAs.…”
Section: Mechanismsmentioning
confidence: 99%
“…Significantly, the bending motions show abilities in kicking, hooking, and grasping. 117 , 120 , 123 , 125 , 142 141 , For example, Tabassian et al. fabricated high-performance grapple robots consisting of four ionic actuator arms; the hybrid electrodes are composed of hollow tubular graphene mesh (GM) and N-doped crumpled RGO (NG).…”
Section: Mechanismsmentioning
confidence: 99%
“…Wang et al reported electrothermal actuators based on rGO/Ag particle composites and polyimide. 76 Hu et al created an rGO-CNT/PDMS bimorph using a high-temperature curing method. 77 Due to the high thermal conductivity and optical absorption of the rGO-CNT film and thermal stresses in the bimorph, large magnitude and fast actuation could be achieved.…”
mentioning
confidence: 99%
“…The wavelength-dependent plasmonic excitation of Au NRs was used to drive photothermal reconfiguration and shape change including the demonstration of a walking spider robot (Figure g,h). Wang et al reported electrothermal actuators based on rGO/Ag particle composites and polyimide . Hu et al created an rGO-CNT/PDMS bimorph using a high-temperature curing method .…”
mentioning
confidence: 99%